2009
DOI: 10.1371/journal.pone.0004451
|View full text |Cite
|
Sign up to set email alerts
|

Compactness Determines the Success of Cube and Octahedron Self-Assembly

Abstract: Nature utilizes self-assembly to fabricate structures on length scales ranging from the atomic to the macro scale. Self-assembly has emerged as a paradigm in engineering that enables the highly parallel fabrication of complex, and often three-dimensional, structures from basic building blocks. Although there have been several demonstrations of this self-assembly fabrication process, rules that govern a priori design, yield and defect tolerance remain unknown. In this paper, we have designed the first model exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 19 publications
(22 reference statements)
1
31
0
Order By: Relevance
“…However, suspected decreased susceptibility of ACT or, at least, longer parasite clearance times have been described in Cambodia [11-14]. In addition, prior therapy by amodiaquine-containing ACT selected reduced response to monodesethylamodiaquine, suggested that amodiaquine-containing regimens may rapidly lose efficacy in Africa [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, suspected decreased susceptibility of ACT or, at least, longer parasite clearance times have been described in Cambodia [11-14]. In addition, prior therapy by amodiaquine-containing ACT selected reduced response to monodesethylamodiaquine, suggested that amodiaquine-containing regimens may rapidly lose efficacy in Africa [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a cruciform was almost always chosen to self-fold a cube. However, a recent study of the self-folding of all 11 nets for the cube and octahedron revealed that different nets fold through different pathways and have different yield (29). In particular, it was found that compact nets had higher yield.…”
mentioning
confidence: 99%
“…Given these considerations, four truncated faces with a metal pad thickness of 4.9 lm and a gap spacing of 7.5 lm were used to obtain 3D structures on an underlying conducting channel. Other researchers investigating the self-folding process for complex structures, such as dodecahedra, icosahedra, and truncated octahedra, found compactness in the 2D pattern to heavily influence folding yields 41 and can be used as a design criterion. 42 Another interesting investigation describes the hierarchy of assembly steps to form microcontainers.…”
Section: Methodsmentioning
confidence: 99%